General Arrangements to Borrow. (Policy Papers; Policy Paper ;, 2017)
This notification summarizes the outcome of consultations with Washington-based representatives of participants in the General Arrangements to Borrow (GAB) on a possible renewal of the GAB decision. By way of background, the GAB was established in 1962 and is a standing agreement between the Fund and 11 participants to supplement the Fund's quota resources (see Box 1). The GAB decision stipulates that the arrangements are subject to periodic renewal, and that decisions on renewal must be taken one year prior to expiration. The last renewal became effective in December 2013. Accordingly, the Fund would need to adopt a decision on renewal not later than twelve months before the end of the current period, id est, not later than December 25, 2017.